INFORMATION TECHNOLOGIES MEANS IN EARLY CHILDHOOD DEVELOPMENT - ЧОБАН-ПИЛЕЦКАЯ, Антонина (Acta et Commentationes, Sciences of Education, 2019)
The article is devoted to the problem of introduction of information technologies into the system of the preschool education and training. The article raises concrete questions about the use of information technologies in the development of a young child. It is analyzed the modern views of scientists regarding this problem. Methods for preparing a professionally competent specialist who is able to apply and implement information technologies tools in the system of preschool education are proposed.